Gabaergic and opioid receptors mediate the facilitation of NaCl intake induced by α₂-adrenergic activation in the lateral parabrachial nucleus - Andrade, Carina Aparecida Fabricio de [UNESP]; Oliveira, Lisandra Brandino de; Andrade-Franzé, Glaucia Maria Fabricio de [UNESP]; Luca Júnior, Laurival Antonio de [UNESP]; Colombari, D. S. A. [UNESP]; Menani, J. V. [UNESP] (Elsevier, 2014)
Alpha2-adrenergic, gabaergic or opioidergic activation in the lateral parabrachial nucleus (LPBN) increases sodium intake. In the present study, we investigated the effects of single or combined blockade of opioidergic and gabaergic receptors in the LPBN on the increase of 0.3 M NaCl intake induced by 2-adrenoceptor activation in the LPBN. Male Holtzman rats (n = 5–9/group) with cannulas implanted bilaterally in the LPBN were treated with the diuretic furosemide (10 mg/kg b wt.) combined with low dose of the angiotensin converting enzyme inhibitor captopril (5 mg/kg b wt.) subcutaneously. Bilateral injections of moxonidine (alpha2-adrenergic/imidazoline receptor agonist, 0.5 nmol) into the LPBN increased furosemide + captopril-induced 0.3 M NaCl intake (25.8 ± 1.4, vs. vehicle: 3.8 ± 1.1 ml/60 min). The opioidergic receptor antagonist naloxone (100 nmol) or the GABAA receptor antagonist bicuculline (5 nmol) injected into the LPBN partially reduced the increase of 0.3 M NaCl intake produced by LPBN moxonidine (11.8 ± 4.0 and 22.8 ± 4.5, respectively, vs. vehicle + moxonidine: 31.6 ± 4.0 ml/60 min, respectively). Similar to the treatment with each antagonist alone, the combined injections of naloxone (100 nmol) and bicuculline (5 nmol) into the LPBN also partially reduced moxonidine effects on 0.3 M NaCl intake (15.5 ± 6.5 ml/60 min). The GABAB receptor antagonist saclofen (5 nmol) injected into the LPBN did not change the effects of moxonidine on 0.3 M NaCl intake (24.3 ± 7.8 ml/120 min). These results suggest that the increase of 0.3 M NaCl intake by 2-adrenergic receptor activation in the LPBN is partially dependent on GABAA and opioid receptor activation in this area.
Keywords: Sodium appetite; Adrenergic; GABA; Opioid; Dehydration; Thirst